Determinants of Green Accounting, Environmental Performance and Environmental Costs on Financial Performance in Indonesia - Hestiana Devi; Lukman Effendy (Cita Konsultindo Research Center, 2024)
The purpose of this study was to determine the effect of environmental performance, environmental costs, and green accounting on the financial performance of companies in Indonesia. The research population consists of manufacturers listed between 2020-2022 on the Indonesia Stock Exchange. Purposive sampling was used to choose a sample of 34 companies. Panel data regression statistics were tested with the EViews 12 program. The study’s conclusions demonstrate that environmental costs have a significant effect on financial performance, but green accounting and environmental performance do not significantly affect financial performance. This research implies that companies develop regulations that encourage utilizing green accounting to enhance the company’s environmental performance. If a company implements a stricter environment, it can improve operational efficiency and increase investor and stakeholder confidence.